PERAN GKJ PEDAN DALAM MEMBANGUN TOLERANSI ANTARAGAMA DI KECAMATAN PEDAN - Natanael Krisna Narayana; Eliana Setyanti (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
ABSTRACT Religious diversity in Indonesia requires continuous efforts to strengthen tolerance in order to maintain harmonious social life. Although numerous studies have examined interreligious tolerance, research specifically addressing the role of churches at the local level through John Hick's perspective of religious pluralism remains limited. This study aims to analyze the role of the Gereja Kristen Jawa (GKJ) Pedan in promoting interreligious tolerance in Pedan District, Klaten Regency. The study employed a qualitative approach using a descriptive method within an interpretive paradigm. Data were collected through observation, in-depth interviews, and documentation involving the pastor, church administrators, congregation members, religious leaders, and community leaders selected using purposive sampling. Data analysis followed the Miles, Huberman, and Saldaña interactive model, consisting of data condensation, data display, and conclusion drawing and verification. The findings indicate that GKJ Pedan promotes interreligious tolerance through active participation in social activities, interfaith communication, and the reinforcement of local wisdom values that foster harmonious community relations. The study further demonstrates that John Hick's perspective of religious pluralism provides a relevant framework for understanding the practice of interreligious tolerance at the community level while enriching scholarly discussions on the contribution of churches to fostering an inclusive society. ABSTRAK Keberagaman agama di Indonesia menuntut penguatan praktik toleransi untuk menjaga kehidupan masyarakat yang harmonis. Meskipun kajian mengenai toleransi antarumat beragama telah banyak dilakukan, penelitian yang secara khusus mengkaji peran gereja pada tingkat lokal melalui perspektif religious pluralism John Hick masih relatif terbatas. Penelitian ini bertujuan menganalisis peran Gereja Kristen Jawa (GKJ) Pedan dalam membangun toleransi antarumat beragama di Kecamatan Pedan, Kabupaten Klaten. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif dalam paradigma interpretatif. Data dikumpulkan melalui observasi, wawancara mendalam (in-depth interview), dan dokumentasi terhadap pendeta, pengurus gereja, jemaat, tokoh agama, serta tokoh masyarakat yang dipilih menggunakan teknik purposive sampling. Analisis data menerapkan model Miles, Huberman, and Saldaña yang meliputi data condensation, data display, serta conclusion drawing and verification. Hasil penelitian menunjukkan bahwa GKJ Pedan membangun toleransi melalui keterlibatan dalam kegiatan sosial, komunikasi lintas agama, serta penguatan nilai kearifan lokal yang mendorong hubungan masyarakat yang harmonis. Temuan penelitian menegaskan bahwa perspektif religious pluralism John Hick relevan dalam menjelaskan praktik toleransi yang berkembang pada tingkat komunitas sekaligus memperkaya kajian mengenai kontribusi gereja dalam membangun kehidupan masyarakat yang inklusif.